Targeted Analysis of Common Spelling Errors among Grade Six Pupils - Nicolas, Joanne Nerissa Castro; Critica, Jasmin Moralidad (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
Spelling errors are the most common inaccuracies in the writing of ESL learners. Despite the numerous studies on writing, teaching spelling as a research topic has often been overlooked. The primary objectives of this mixed method study are to describe the common spelling errors of grade 6 pupils of an all-girls school in Metro Manila post-pandemic, identify teaching strategies to minimize spelling errors and propose recommendations for teaching spelling. First, spelling tests and student handwritten essays were analyzed for spelling errors, which were later categorized using Cook’s classification. Second, interviews with Language teachers to identify teaching strategies were held, determining key themes and best practices in spelling instruction. The results indicated that students committed spelling errors mostly by omission, substitution, and insertion, and the strategies to enhance spelling skills include utilizing visuals, engaging students through interactive materials and collaborative activities, and using the words in context. Based on the findings, it is recommended to consider the following in crafting a spelling program: a fundamental list of commonly misspelled words following the rule-based system, a bank of effective strategies to expose students to words in context and engage them for active learning, a continuous assessment of spelling student abilities, and evaluation of the spelling program.